ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Totok Dewayanto (STIE Pelita Nusantara Semarang, 2011)
This study aims to analyze and provide empirical evidence of the influence of the financial condition of the company, company size, previous audit opinion, auditor tenure client, opinion shopping and auditor quality on the probability of receiving going-concern opinion. Hipotesisi proposed (1) corporate financial conditions affect the probability of accepting the opinion of going concern, (2) firm size effect on acceptance going-concern opinion, (3) previous audit opinion effect on acceptance going-concern audit opinion, (4) client auditor tenure influence on acceptance going-concern audit opinion, (5)opinion shopping influence on acceptance going-concern audit opinion, (6) affect the reception quality of the auditor going-concern audit opinion.This study used 28 manufacturing companies listed on the Stock Exchange 2006-2009. samples obtained by purposive sampling. Data were analyzed using logistic regression analysis.The results showed that firm size, auditor tenure client, opinion shopping and audit quality has no effect on acceptance going-concern opinion. While the company’s financial condition and the previous audit opinion effect on acceptance going-concern audit opinion.